Shortest path from Bandar Tun Razak to Berjaya Times Square using Dijkstra Algorithm / Nur Syuhada Muhammat Pazil ... [et al.] - Muhammat Pazil, Nur Syuhada; Mahmud, Norwaziah; Jamaluddin, Siti Hafawati; Mustafa, Nur Farasyaqirra (UiTM Cawangan Perlis, 2020)
The shortest path is an issue that involves the route from one point (nodes) to another. It is to find a path with a minimum travelling time. Nowadays, traffic problems have affected many transport users especially in Kuala Lumpur area. The time wasted on the road causes a lot of problems to the users. Furthermore, the costs between two destinations are rather expensive. Therefore, the inability of users to use the shortest path has attracted the researcher to propose several travel alternatives to overcome this problem. In addition, this study will help to improve the efficiency of the road and make people want to use it more often. The objectives of this study are to find the shortest path from Bandar Tun Razak to Berjaya Times Square and to cut down the cost between these two destinations. The time of the shortest path problem and the cost problem are drawn separately. Moreover, Dijkstra algorithm is applied to find the shortest path. The shortest path is calculated by using C programming of Dev C++. Nevertheless, both time and cost of shortest path are constructed in different paths. The time and cost of the journey are described by driving a car from Bandar Tun Razak to Lebuhraya SMART to Kampung Pandan, then Berjaya Times Square. The total time taken is 23 minutes (RM8.00), whereas, the cost is based on the shortest path from Bandar Tun Razak to Taman Maluri to Seasons Tower and Berjaya Times Square. The minimum cost is RM4.00 (30 minutes).